Two novel loci underlie natural differences in Caenorhabditis elegans abamectin responses. - Kathryn S Evans; Janneke Wit; Lewis Stevens; Steffen R Hahnel; Briana Rodriguez; Grace Park; Mostafa Zamanian; Shannon C Brady; Ellen Chao; Katherine Introcaso; Robyn E Tanny; Erik C Andersen (PLoS Pathogens, 2021)
Parasitic nematodes cause a massive worldwide burden on human health along with a loss of livestock and agriculture productivity. Anthelmintics have been widely successful in treating parasitic nematodes. However, resistance is increasing, and little is known about the molecular and genetic causes of resistance for most of these drugs. The free-living roundworm Caenorhabditis elegans provides a tractable model to identify genes that underlie resistance. Unlike parasitic nematodes, C. elegans is easy to maintain in the laboratory, has a complete and well annotated genome, and has many genetic tools. Using a combination of wild isolates and a panel of recombinant inbred lines constructed from crosses of two genetically and phenotypically divergent strains, we identified three genomic regions on chromosome V that underlie natural differences in response to the macrocyclic lactone (ML) abamectin. One locus was identified previously and encodes an alpha subunit of a glutamate-gated chloride channel (glc-1). Here, we validate and narrow two novel loci using near-isogenic lines. Additionally, we generate a list of prioritized candidate genes identified in C. elegans and in the parasite Haemonchus contortus by comparison of ML resistance loci. These genes could represent previously unidentified resistance genes shared across nematode species and should be evaluated in the future. Our work highlights the advantages of using C. elegans as a model to better understand ML resistance in parasitic nematodes.